Changes in CD4+CD69, CD8+CD69 and monocytes CD14- following 2 days of high intensity interval training and after one day of recovery in well trained junior cross-country skiers - Kadi, F.; Wernstedt, I.; Gustafsson, H.; Folkesson, M.; Fäldt, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
High intensity interval training (HIT) is commonly used to improve endurance performance. In this respect, two bouts of HIT per day are occasionally performed by competitive athletes engaged in endurance sports. Knowledge about immunological changes during intensive training periods is important from both a scientific and a practical point of view. The aim of this study was to investigate changes in CD4+CD69-, CD8+CD69- and monocytes CD14- during 2 days with 2HIT sessions per day followed by one day of recovery. Methods 5 male well-trained junior cross-country skiers completed two days with two HIT sessions a day followed by one recovery day. The intensity of the intervals was 85-95 % of maximum heart rate. Blood samples were taken before and 30 min after (active cool down) the first session and before and 30 min after the second session on training days 1 and 2 and following 14 h (one night sleep) and 38h (2 nights sleep) of recovery after HIT 2 on day 2. The resting period between 2 training bouts was 5h30min. Whole blood was mixed with monoclonal antibodies and incubated 30 minutes at 4°C and FACS Lysing Solution was added for removal of erythrocytes. Cells were then resuspended in FACSFlow and stored at 4°C before analysing. The samples were analysed in a FACSscan with 4-colour within 48 h. Results Compared to initial levels, CD4+CD69- and CD8+CD69- decreased significantly after day1 and returned to initial levels after one night sleep (14h recovery). After day 2 , CD4+CD69- and CD8+CD69- decreased significantly compared to initial levels and remained significantly lower following 14 h recovery but returned to initial levels following 38 h recovery. Monocytes CD14- were not altered following training day 1 but increased following HIT 2 on day 2 and remained higher than initial levels after 14 h recovery. Monocytes CD14- returned to baseline levels after 38h recovery. Discussion/conclusion Based on the immunological variables measured in this study, it is suggested that body homeostasis is restored 14 h after 2 HIT sessions a day but not after 2 consecutive days with the same training load. However, 38 h after the last training session homeostasis is restored.